2014
DOI: 10.1136/heartjnl-2013-305030
|View full text |Cite
|
Sign up to set email alerts
|

Public access defibrillation remains out of reach for most victims of out-of-hospital sudden cardiac arrest

Abstract: IntroductionPublic access defibrillation (PAD) prior to ambulance arrival is a key determinant of survival from out-of-hospital (OOH) cardiac arrest. Implementation of PAD has been underway in the UK for the past 12 years, and its importance in strengthening the chain of survival has been recognised in the government's recent ‘Cardiovascular Disease Outcomes Strategy’. The extent of use of PAD in OOH cardiac arrests in the UK is unknown. We surveyed all OOH cardiac arrests in Hampshire over a 12-month period t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(59 citation statements)
references
References 23 publications
4
53
1
1
Order By: Relevance
“…[19][20][21][22][23][24] Only via critical analysis of prospectively registered data, results may improve and costs may represent good value for (public) money. Second, device malfunctions occasionally occur and should be detected in a timely fashion by post-market surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24] Only via critical analysis of prospectively registered data, results may improve and costs may represent good value for (public) money. Second, device malfunctions occasionally occur and should be detected in a timely fashion by post-market surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…(2,3) Public access defibrillation (PAD) programmes have been established to empower bystanders to deliver early defibrillation, but have so far produced ambivalent results. (3)(4)(5) Although the evidence to support the benefits of public access automated external defibrillators (AEDs) is strong, (3,(5)(6)(7) unfortunately these lifesaving devices are often used only in a minority of SCA cases, even in areas where they are readily available. (4,7) Education of the public is one of the crucial factors to increase awareness, willingness and knowledge to use AEDs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that PAD programs in railways, casinos, and airports in the United States, Europe, and Japan have improved survival in patients with OHCA 3, 4, 5, 6, 7. Despite this, a study showed that PAD was deployed successfully in less than 2% of OHCA, suggesting that there are still areas that can improve their access and deployment of PAD 8. All of the studies of PAD programs have been in the United States, Europe, and Japan.…”
Section: Introductionmentioning
confidence: 99%